1970
DOI: 10.1073/pnas.67.2.724
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Liver Glutamate Dehydrogenase: Tentative Amino Acid Sequence; Identification of a Reactive Lysine; Nitration of a Specific Tyrosine and Loss of Allosteric Inhibition by Guanosine Triphosphate

Abstract: Abstract. A tentative but almost complete amino acid sequence for the subunit peptide chain of bovine liver glutamate dehydrogenase indicates a minimal size of 506 residues with a molecular weight of 56,100, in accord with the physical size of the subunit of 55,900. Inactivation with pyridoxal 5'-phosphate, followed by reduction with sodium borohydride, has permitted identification of the essential lysine as residue 97. Nitration of tyrosine-412 is accompanied by loss of the allosteric inhibitory effect of gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(27 citation statements)
references
References 13 publications
(2 reference statements)
1
25
0
1
Order By: Relevance
“…Earlier studies on in vitro tyrosine nitration of bovine GDH with tetranitromethane showed that nitration of one tyrosine residue per subunit (Tyr412), which later was correctly identified as Tyr464 (Figure 2), does not affect the activity of the enzyme but decreases its response to inhibition by GTP [152,153,154]. In the resolved bovine GDH structure, Tyr464 is located in the middle of the antennae region, which suggests that the nitration of this residue may abrogate conformational changes of the antennae, thus perturbing the allosteric regulation of GDH [66].…”
Section: Post-translational Modifications Of Gdh and Their Biologimentioning
confidence: 99%
“…Earlier studies on in vitro tyrosine nitration of bovine GDH with tetranitromethane showed that nitration of one tyrosine residue per subunit (Tyr412), which later was correctly identified as Tyr464 (Figure 2), does not affect the activity of the enzyme but decreases its response to inhibition by GTP [152,153,154]. In the resolved bovine GDH structure, Tyr464 is located in the middle of the antennae region, which suggests that the nitration of this residue may abrogate conformational changes of the antennae, thus perturbing the allosteric regulation of GDH [66].…”
Section: Post-translational Modifications Of Gdh and Their Biologimentioning
confidence: 99%
“…The dialyzed enzyme was stored in aliquots at -75°C and was thawed immediately prior to use. A molecular mass of 56.1 kDa for the six identical peptide chains of the active form of glutamate dehydrogenase was used in the calculations [21].…”
Section: Methodsmentioning
confidence: 99%
“…Similarities are indicated from comparisons without knowledge of enzyme structures (1)(2)(3) and from comparisons of short regions of glyceraldehyde phosphate dehydrogenase (GPDH), liver alcohol dehydrogenase (LADH), yeast alcohol dehydrogenase (YADH), lactate dehydrogenase (LDH), or glutamate dehydrogenase (GDH) (4)(5)(6)(7)(8)(9)(10). Long segments of possible but distant homology are found between GPDH and LADH (11) or GDH (12).…”
mentioning
confidence: 99%